Adenovirus surveillance in wild carnivores from Brazil - Lial, Henrique Christino; Navas-Suárez, Pedro Enrique; Ewbank, Ana Carolina; Exposto Novoselecki, Helena; Ferreira-Machado, Eduardo [UNESP]; dos Santos Cirqueira, Cinthya; de Azevedo Fernandes, Natália Coelho Couto; Esperón, Fernando; Catão-Dias, José Luiz; Sacristán, Carlos (Elsevier, 2022)
Landscape transformation favors the spread of new pathogens that can be shared between domestic and wild animals. Certain adenoviruses (e.g., canine adenovirus 1 and 2, family Adenoviridae) can infect domestic and wild carnivores. In domestic canids, these viruses are associated with hepatic and respiratory diseases (among others). Nevertheless, information regarding adenovirus pathogenicity and molecular features in wild carnivores is still limited. Herein we surveyed adenovirus in free-ranging carnivores from Brazil. Total DNA was extracted from and subsequently tested by a nested panPCR in spleen and/or lung of 52 carnivores, representing species of the following families: Canidae (n = 4), Felidae (n = 3), Mustelidae (n = 2) and Procyonidae (n = 2). The obtained sequences were compared to others available at GenBank. Available tissue samples from the positive cases were evaluated histopathologically. One out of 52 (1.9%, CI 95%, 0.0–5.7%) carnivores was positive; a roadkilled ocelot (Leopardus pardalis). The obtained sequence presented a low deduced amino acid (78.1%) similarity with the closest adenovirus, identified in a pinniped from the United States of America. This fact and its detection in a novel host suggest it may be representative of a novel species and denominated ocelot adenovirus 1. None of the gross and microscopic findings of the positive case were associated with adenovirus. To the authors' knowledge, this is the first report of adenovirus in wild felids of South America and the second worldwide. Further studies are necessary to assess the epidemiology and potential pathogenicity of this agent in wild carnivores.
Keywords: Landscape transformation; Ocelot; Roadkill; South America; Viral discovery; Wildlife